Measuring the Level of Socialization in Children with Autism Spectrum Disorder - Khaustov A.V; Rudneva E.V (Moscow State University of Psychology and Education, 2016)
Difficulties with socialization common for children with autism spectrum disorder (ASD) are a serious problem for their inclusion into educational settings. These socialization deficits are basically related to underdeveloped social skills. The paper describes a study aimed at revealing the level of socialization in children with ASD. The study involved 117 children aged 5-7 years and their parents. The children's socialization level was measured with the Vineland Adaptive Behavior Scale. The outcomes showed that most children with ASD display low levels of socialization resulting in their inability to adequately communicate and cooperate with other people as in play, as in everyday life. Two factors were found to affect the level of socialization in the children: deficit of motivation and specific cognitive impairments. The paper argues for the necessity of developing a program for psychologi- cal and educational assistance aimed at forming social skills in children with ASD.